Structural Competency in Simulation-Based Health Professions Education: A Call to Action and Pragmatic Guide - Sagalowsky, Selin T; Woodward, Hilary; Agnant, Joanne; Bailey, Bart; Duncan, Ellen; Grad, Jennifer; Kessler, David O (Simulation in healthcare : journal of the Society for Medical Simulation, 2024)
Simulation-based health professions educators can advance diversity, equity, and inclusion by cultivating structural competency, which is the trained ability to discern inequity not only at an individual level, but also at organizational, community, and societal levels. This commentary introduces Metzl and Hansen's Five-Step Model for structural competency and discusses its unique applicability to the metacognitive underpinnings of simulation-based health professions education. We offer a pragmatic guide for simulation-based health professions educators to collaboratively design learning objectives, simulation cases, character sketches, and debriefs in which structural competency is a simulation performance domain, alongside patient management, resource usage, leadership, situational awareness, teamwork, and/or communication. Our overall goal is to promote a paradigm shift in which educators are empowered to partner with patients, colleagues, and communities to recognize, learn about, and challenge the factors driving health inequities; a skill that may be applied to a broad range of health professions education within and outside of simulation.